Characterizing cognitive function during relapse in multiple sclerosis. (November 2014) - Benedict, Ralph HB; Morrow, Sarah; Rodgers, Jonathan; Hojnacki, David; Bucello, Margaret A; Zivadinov, Robert; Weinstock-Guttman, Bianca
Objective: To characterize neuropsychological (NP) test performance during multiple sclerosis (MS) relapse and recovery. Methods: Clinical status was assessed with NP testing and Expanded Disability Status Scale (EDSS) in 24 relapsing patients, and 24 individually-matched, stable controls. All presented with cognitive symptoms as indicated by patient, clinician or caregiver perceived decline, but were free of optic neuritis, ataxia and upper extremity weakness that could compromise NP testing. The presence of enhancing magnetic resonance imaging (MRI) lesions was considered confirmatory of relapse. Relapsing patients were treated with corticosteroids. NP testing and EDSS were compared to pre-relapse baseline levels, and three-month, post-relapse, follow-up. Results: Analyses revealed significant decline on the Symbol Digit Modalities Test (SDMT) ( p =0.005) and worsening on EDSS ( p =0.019). Impairment was observed at the point of relapse in cases but not controls. The groups were no longer different at three-month follow-up. The increment of decline on SDMT was 3.5 raw score points, or roughly 6%. Conclusions: This is the first study to assess NP status changes during MS relapse using well established, reliable metrics. The presence of a clinically meaningful event is substantiated by decline in NP testing, observed or reported cognitive change, and in a subset of patients, gadolinium-enhancing MRI lesions.